Major element, trace element and Sr isotope data of selected magmas from the Aegean, Greece - Anna Schaarschmidt; Karsten M Haase; Panagiotis C Voudouris; Vasilios Melfos; Reiner Klemd (PANGAEA, 2020)
The dataset contains whole rock geochemical data of Oligocene to Miocene volcanic and plutonic rocks from the Aegean region, Greece. The samples originate from outcrops in northeast Greece near Alexandropoulos and from the island of Limnos. Major and trace elements were measured using X-ray fluorescence spectrometry (XRF) and Quadrupole Inductively Coupled Plasma Mass Spectrometry (ICP-MS), respectively. The Sr and Nd isotopes were measured using thermal ionization multi-collector mass spectrometry (TIMS). All analyses were carried out at the GeoZentrum, Friedrich-Alexander-Universität in Erlangen. The data complement published geochemical data of magmatic rocks of the Aegean, which reveal a migration of the magmatic activity from NE to SW during the past 30 Ma.